Social Groups behind Biblical Traditions Identity Perspectives from Egypt, Transjordan, Mesopotamia, and Israel in the Second Temple Period - Hensel, Benedikt; Adamczewski, Bartosz; Nocquet, Dany; Nocquet, Dany; Adamczewski, Bartosz (Mohr Siebeck, 2023)
Soziale Gruppen hinter biblischen Traditionen. Identitätsperspektiven aus Ägypten, Transjordanien, Mesopotamien und Israel aus der Zeit des Zweiten Tempels.
PublicationDate: 20230616
Keywords: early Judaism -- Elephantine -- Making of the Pentateuch -- judiciallearning -- Making of the Hebrew Bible -- Formative period of Judaism -- Biblical Israel -- Fortführung -- Early Judaism -- Altes Testament -- Antike -- Antike Religionsgeschichte -- Old Testament -- History of Ancient Religions -- Antiquity